PERCEPTIONS OF PHYSICAL EDUCATION TEACHERS AT STATE SCHOOLS WITH THE INCLUSION OF STUDENTS WITH DISABILITIES (Fiep Bulletin - online, 2015)
The aim of this study was to investigate the pedagogical practices of teachers of Physical Education at state schools in a Brazilian city, regarding the inclusion of students with disabilities in their classes. For this purpose, a questionnaire adapted from models already validated by Sideridis and Chandler (1997) and Kozub and Porretta (1998) for a sample of nine (9) Physical Education teachers working in state schools was used. The results revealed that although the majority of teachers report not to have enough knowledge to meet students with disabilities, they like these students in their classes, and intend to take courses to increase their knowledge. It was concluded that the inclusion that takes place in physical education classes in tihs city happens due to the practice of the teacher rather than to the organization of the inclusion process and its implications.
Keywords: Inclusion. Disabilities. Physical Education. Regular Teaching System